Effect of Disinfection and Accelerated Aging on Color Stability of Colorless and Pigmented Facial Silicone - Pesqueira, Aldieris Alves [UNESP]; Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP]; Haddad, Marcela Filie [UNESP]; Ribeiro, Paula do Prado; Coelho Sinhoreti, Mario Alexandre; Marcal Mazza Sundefeld, Maria Lucia (Wiley-Blackwell, 2011)
Purpose: The aim of this study was to evaluate the color stability of a facial silicone with different pigmentations submitted to disinfection and accelerated aging.Materials and Methods: Sixty replicas were fabricated with the silicone Silastic MDX 4-4210 and divided into three groups: no pigmentation, pigmentation with makeup powder, and pigmentation with ceramic powder. Half the replicas of each group were submitted to disinfection with Efferdent and the other with neutral soap for 60 days (n = 10). After this period, all replicas were inserted in a chamber for accelerated aging of nonmetallic specimens. The color measurements were carried out initially, after disinfection, and after accelerated aging (252, 504, 1008 hours). Color stability was evaluated through spectrophotometry. The values were submitted to ANOVA and the means to Tukey's test (p < 0.01Results: The specimens disinfected with neutral soap exhibited higher Delta E values regardless of the type of pigmentation. The colorless replicas and the specimens pigmented with ceramic exhibited a statistically significant difference between the methods of disinfection in all periods. The specimens pigmented with makeup powder did not demonstrate a statistically significant difference.Conclusions: The ceramic pigment presented greater color stability regardless of disinfection and period. on the other hand, the makeup pigment exhibited the highest values of chromatic alteration.
Keywords: Maxillofacial prosthesis; color; prosthesis pigmentation; disinfection